Contribution of biofertiliser (Frateuria auranta) in an integrated potassium management package on growth of apple banana - Nowembabazi, Anna; Taulya, Godfrey; Tinzaara, William (Scientific Research Publishing, Inc., 2021)
Bananas demand high amounts of potassium for optimal growth and productivity, yet deficiencies are widespread amid the low input production strategy of smallholder farmers in Uganda. Of the potassium pool in the soil, 90% - 98% is unavailable for plant uptake. Judicious application of fertilisers is required to alleviate soil fertility problems complemented with manures and biofertilisers in an integrated nutrient management (INM) package. Biofertilisers such as potassium solubilising bacteria (KSB) have potential to solubilise unavailable forms of K in soil to forms that are readily absorbed by the plants. However, the added value of each component in this integrated K management package in apple bananas is not known. Therefore, an experiment was set up to quantify the relative contribution of mineral K, manure and KSB on the growth of apple bananas. Potted tissue culture plantlets of apple banana (cv. Sukali ndiizi) were used. The treatments comprised of a full factorial combination of mineral fertiliser (Muriate of potash, 60% K2O), animal manure and KSB (Frateuria auranta). The manure and muriate of potash were applied to supply a total of 150 kg⋅K⋅ha−. Soil microbiological assays were run to evaluate the contribution of indigenous microbial K solubilising activity in the soil to the experimental INM package. Data on pseudostem height, girth at collar and 30-cm height, leaf length and width at the widest point were collected once a week for 24 weeks. Bacillus, Pseudomonas and Frateuria were present as indigenous KSBs in the soil. The biofertiliser applied as F. auranta solubilised 7.4 mg⋅K⋅l−1 (6.2 mg⋅K⋅kg−1) from soil minerals. The integrated K management package significantly (p < 0.001) increased the above ground biomass and leaf area of potted apple bananas by up to 57.5% compared to no input. The Study recommends an economic analysis study to determine the integrated K management package that would suit the resource constrained smallholder farmers.